Methods of Estimating Inventories Training for SMA Kristen Yusuf Students - Yanti Yanti; Yoan Tobing; Pricillia Anastasia (Transpublika Publisher, 2025)
The partner in this community services (PKM) is SMA Kristen Yusuf. This school was chosen because it has a conducive learning environment and good support from the school for academic activities outside of school hours. Every year, the Partner always screens and prepares outstanding students to participate in accounting competitions held by various national-level universities. Therefore, the problem currently being experienced by the Partner is that the Partner needs additional accounting materials for the purposes of the competition, including inventory valuation using the estimation method. The training activity was held face-to-face (onsite) on Thursday, September 25, 2025, from 3:05 PM to 4:40 PM WIB, attended by 4 students from grades 12 and 11. The training was orderly, focused, and interactive. Participants enthusiastically answered questions posed by the PKM team. Based on questionnaire results, most students expressed satisfaction with the training. They felt the material was delivered in an easy-to-understand manner, the classroom atmosphere was pleasant, and the instructor was able to explain concepts clearly. Several students also stated that the training made them more interested in learning accounting basics independently. There are three outputs from this training: Publication Articles, Intellectual Property Rights (IPR), and Products/Prototypes.